Rocky relief in some caves of "Notranjsko podolje" - Slabe, Tadej (Acta carsologica, 1996)
Rocky relief frequently serves as important speleogenetical evidence. This is also confirmed by study of rocky relief in selected caves of Notranjsko podolje. The results may be used to define the origin and development of this morphogenetically consistent karst area.
Keywords: karst; kras (geologija); kraške jame; kraški pojavi; List of caves in Slovenia; Notranjsko podolje